Voluntary activation and central activation failure in the knee extensors in young women and men - Miller, M.; Holmbäck, A. M.; Downham, D.; Lexell, J. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Quadriceps muscle weakness is common after knee injuries. This weakness is caused, in part, by reduced voluntary activation (VA) because of central activation failure (CAF). Superimposed electrical stimulation techniques are used to assess VA and to detect CAF. The aim of this study was to assess VA during knee extension in young healthy women and men, and to evaluate subjective discomfort from the electrical stimulation. The quadriceps muscle in six young healthy women (mean age 22 years) and six young healthy men (mean age 29 years) was stimulated during maximal voluntary contractions using a 100 Hz pulse train. Data were collected from two test sessions separated by 6-8 days and each session comprised of two trials. A visual analog scale for pain (VAS-pain) was used to evaluate subjective discomfort. Overall, young healthy, moderately active men and women did have the ability to fully activate their knee extensors isometrically, but they did not achieve full activation on every trial. In those trials where a CAF was detected, the degree was small (mean less than 2%), and did not vary between the two test sessions. Subjective discomfort was generally moderate and tolerable (mean VAS-pain score 35 mm). These results will assist the clinical assessment of muscle weakness following a knee injury and facilitate the design and evaluation of appropriate rehabilitation interventions.